Polyurethane graphene nanocomposites with self-healing properties by azide-alkyne click reaction - Akhan, Seda; Oktay, Burcu; Ozdemir, Oguz Kaan; Madakbas, Seyfullah; Apohan, Nilhan Kayaman (ELSEVIER SCIENCE SA, 2020)
Nanocomposites stand out as promising materials in many fields due to their properties such as strength, hardness, thermal stability, and lightness. Introducing self-healing ability to polymer nanocomposites provides new guidelines for strong, sustainable, and durable materials. Microcapsule-based self-healing materials work independently of an external stimulus such as pH, heat, light and solvent. In this paper, we developed autonomously self-healing UV-cured polyurethane graphene oxide nanocomposite coatings by means of efficient and useful copper-catalyzed azide-alkyne (CuAAC) click chemistry. Low molecular weight tetra-arm azide was successfully capsulated within poly(vinyl formal) capsules. Alkyne functional graphene-oxide reinforced nanocomposites containing azide microcapsules were prepared through photo-polymerization. The self-healing ability and anti-corrosion properties of the nanocomposites were studied after the damage occurred. The self-healing experiments show that the microcapsules provided a self-healing efficiency of around 70% after 24 h. Chemical, morphologic, mechanical, and thermal properties of the films were investigated. Furthermore, the electro-chemical analysis of films showed that the microcapsule containing films has a higher polarization resistance and a lower corrosion current.
Keywords: Nanocomposites; Self-healing; Microcapsule; Azide-alkyne click reaction; Graphene oxide; OXIDE; COATINGS; CYCLOADDITION; MICROCAPSULES; DEGRADATION; INHIBITION; CHEMISTRY; HYDROGELS; CORROSION; ENERGY; Materials Science